Diffusion and Adoption of SiBakul Markethub Innovation Free Shipping DIY in the Era of the Covid-19 (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2023)
Covid-19 in Indonesia has resulted in a decrease in income and difficulties in accessing marketing for UMKM. So, there is a need for efforts to restore people’s purchasing power and facilities for marketing UMKM products through online-based services. SiBakul Markethub innovation is a solution to help UMKM problems by providing free shipping facilities. The purpose of this study was to identify and describe the process of diffusion and adoption of SiBakul Markethub innovations in Yogyakarta and how relevant the innovations were to be developed after pandemic. The research method used is descriptive qualitative through interviews, observation, and documentation. The research sample consisted of one DIY PLUT consultant and ten UMKM who were aware of SiBakul Markethub’s innovations. The research sample consisted of one DIY PLUT consultant and ten MSMEs who were aware of SiBakul Markethub’s innovations. SiBakul Markethub innovation is something new, so there is a process diffusion of innovation. There are four elements of the diffusion of innovation, the characteristics of innovation, communication channels, time period and social system. The decision process of acceptance or adoption of innovation according to Rogers consists of five stages including knowledge, persuasion, decision, implementation, and confirmation. The stages of community adoption of SiBakul Markethub vary depending on the adapter category. The results of the diffusion process and innovation adoption have a significant impact on the increase in turnover. SiBakul Markethub innovation is still relevant to be developed after the pandemic because it supports UMKM Go Digital. This research contributes to the development of the innovation diffusion theory by looking at the context of innovation during the Covid-19 pandemic. The practical implications of this research provide insight to stakeholders regarding marketing strategies and service development in dealing with a pandemic situation.
Keywords: diffusion; adoption; SiBakul Markethub; Covid-19 pandemic